Prognostic impact of hepatorenal function in patients undergoing transcatheter tricuspid valve repair - Tetsu Tanaka (Nature Portfolio, 2021)
Abstract Hepatorenal dysfunction is a strong risk factor in patients with heart failure (HF). We investigated the prognostic significance of hepatorenal dysfunction in 172 consecutive patients undergoing transcatheter tricuspid valve repair (TTVR). The model for end-stage liver disease excluding international normalized ratio (MELD-XI) score was calculated as 5.11 × ln(serum total bilirubin [mg/dl]) + 11.76 × ln(serum creatinine [mg/dl]) + 9.44. Patients were stratified into two groups: high (≥ 14) or low (< 14) MELD-XI score, according to the best cut-off value to predict a one-year composite outcome consisting of all-cause mortality and HF hospitalization. Compared to patients with low MELD-XI score (n = 121), patients with high MELD-XI score (n = 51) had a higher incidence of the composite outcome (47.1% vs. 17.4%; p < 0.0001). In the multivariable analysis, the MELD-XI score was an independent predictor of the composite outcome (adjusted hazard ratio: 1.12; 95% confidence interval [CI] 1.05–1.19; p = 0.0003). In addition, post-procedural TR < 3 + after TTVR was independently associated with a reduction in MELD-XI score six months after TTVR (adjusted odds ratio: 3.37; 95% CI 1.09–10.40; p = 0.03). Thus, the MELD-XI score was associated with the risk of one-year composite outcome, consisting of mortality and HF hospitalization, after TTVR and may help the risk stratification in patients undergoing TTVR.